Medresetü’z-Zehra: Bediuzzaman Said Nursi’s Vision of Reconciliatory Education in the Post-Ottoman Era - Purwaningtyas, Dhita Ayomi; Yemmardotillah, M (An-Nuha, 2025)
The collapse of the Ottoman Empire and the rise of the Turkish Republic created deep epistemological and sociopolitical ruptures, marginalising religious education and ethnolinguistic diversity. In response, Said Nursi proposed Medresetü’z-Zehra—a visionary model of education aimed at reconciling religious and rational sciences within a pluralistic framework. This study explores Medresetü’z-Zehra as a postcolonial educational project addressing epistemological fragmentation and cultural homogenisation. Employing a qualitative historical-analytical method, the research analyses primary texts from Nursi's Risale-i Nur and contextualises his vision against Ottoman reforms and Republican secular policies. The findings reveal that Medresetü’z-Zehra represents a profound model of epistemological integration, promoting unity of knowledge (wahdat al-'ilm) and ethical formation while affirming linguistic and cultural plurality. In conclusion, Nursi's educational philosophy offers a reconciliatory framework for contemporary Muslim societies seeking to harmonise tradition and modernity without sacrificing diversity and moral integrity.